2019
DOI: 10.1111/csp2.24
|View full text |Cite
|
Sign up to set email alerts
|

Conservation implications of misidentification and killing of protected species

Abstract: Killing protected species mistaken for morphologically similar quarry species, or species with weaker protection, can hinder their conservation. Despite policy aims to reduce threats from illegal killing, information is lacking on susceptible species, conservation impacts and the identification accuracy of hunters. We examined the ability of hunters (n = 232) in Arctic Russia to identify the endangered Northwest European Bewick's swan Cygnus columbianus bewickii using photographs. Only 14% (n = 33) identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The spatial pattern of declines and increases in Bewick's Swan numbers across the winter range are, however, consistent with short-stopping due to climate change, which has caused milder winters across Europe in recent years (Nuijten et al 2020b). Further to the effects of climate, future research into fluctuations in Bewick's Swan numbers should investigate the role that known sources of mortality, such as illegal shooting (Newth et al 2019), could have played in observed decline. In addition, other factors that could have led to deleterious environmental changes in the overwintering grounds, such as the expansion of energy infrastructure that poses collision risk to swans and other large birds, should be considered in future assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial pattern of declines and increases in Bewick's Swan numbers across the winter range are, however, consistent with short-stopping due to climate change, which has caused milder winters across Europe in recent years (Nuijten et al 2020b). Further to the effects of climate, future research into fluctuations in Bewick's Swan numbers should investigate the role that known sources of mortality, such as illegal shooting (Newth et al 2019), could have played in observed decline. In addition, other factors that could have led to deleterious environmental changes in the overwintering grounds, such as the expansion of energy infrastructure that poses collision risk to swans and other large birds, should be considered in future assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Misidentification of a common species for a rare species may lead to an overall reduction in monitoring and conservation of rare and endangered species [3,10], including P. sintoxia. In some cases, misidentifications may lead to a removal or inadvertent killing of an endangered species [10] with the permitting of habitat alteration or destruction during infrastructure construction and development projects (e.g., bridges, roads, pipelines, marinas, etc.).…”
Section: Conservation Implications and Conclusionmentioning
confidence: 99%
“…Misidentification of a common species for a rare species may lead to an overall reduction in monitoring and conservation of rare and endangered species [3,10], including P. sintoxia. In some cases, misidentifications may lead to a removal or inadvertent killing of an endangered species [10] with the permitting of habitat alteration or destruction during infrastructure construction and development projects (e.g., bridges, roads, pipelines, marinas, etc.). Resolving misidentifications of freshwater mussels has become increasingly important (e.g., Inoue et al [16], Beyett et al [19]), as approximately 70% of unionid mussel species in North America are considered at risk of extinction [1].…”
Section: Conservation Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation